Utilization of fly ash in construction industry - Barbhuiya, Salim (NOVA Publishers, 2014)
The use of fly ash improves the performance of concrete in its fresh and hardened states. This enables the concrete industry to use hundreds of millions of tonnes of this by-product material, which would otherwise be landfilled, as a waste. This also allows the concrete producer to design and modify the concrete mix to suit the desired application. The fly ash concrete system offers a holistic approach that can help us to achieve the goals of meeting the rising demands for concrete, enhancement of concrete durability with little or no increase in cost (in some instances reduced cost), and ecological disposal of large quantities of the solid waste products from coal-fired power plants. Several laboratory and field investigations involving concrete containing fly ash had reported to exhibit excellent mechanical and durability properties. However, due its conservative nature the construction industry is still not fully utilizing the potential benefits of using fly ash in concrete production. In this chapter an attempt is made to review first the origin, properties and current knowledge of fly ash as reported in the literature. This is followed by a discussion on the utilisation of fly ash in construction and the potential issues related to their use. Finally, areas of further research have been identified.